Studies on maturity indices of karonda (Carissa carandas L.) fruits (Indian Journal of Arid Horticulture, 2025)
Karonda (Carissa carandas L.) a member of family Apocynaceae is an indigenous fruit of Indian subcontinent. It is an underutilized evergreen thorny bush which thrives well through out Tropical and Subtropical climate (Singh and Singh, 1992) and is also found in Africa, Australia, Srilanka, Thailand, Indonesia and Malaysia mainly in wild form. In India its cultivation was initiated by the European in Kitchen garden to get fruit for jelly preparation. Karonda is known by several vernacular names such as karaunda, Karunda, garinga, krrona, timukhia and gotho in Hindi; Kurumia, Karamcha, Bainchi, Karenja and tair in Bingali; Karauanda and baronda in Marathi; Karamarda and Timbarran in Gujrati; Karamarda, Karamardaka, avinga and vrishnapakphula in Sanskrit; Kendakeri and Kerendokuli in Uriya; waaka and kalivikaya in Telgu and Kalaka and Kalapa in Tamil. It can flourish well on saline, alkaline and other waste lands on which other fruit crops do not thrives well. Karonda is best plant for live fencing that also produces fruits.
Keywords: Subtropical; Apocynaceae; vernacular; flourish; saline